2006
DOI: 10.1366/000370206776342544
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Breakdown Spectroscopy for Ambient Air Particulate Monitoring: Correlation of Total and Speciated Aerosol Particle Counts

Abstract: A statistical analysis of ambient air particle monitoring, namely PM2.5, is presented to elucidate the correlations between laser-induced breakdown spectroscopy (LIBS)-based speciated aerosol monitoring and non-speciated aerosol monitoring (i.e., total particle counts). LIBS was used in a real-time, conditional-processing mode to identify individual aerosol particles containing detectable quantities of either calcium or sodium, as based on the resulting atomic emission signals. Using this technique, real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
(52 reference statements)
0
14
0
1
Order By: Relevance
“…Nonetheless, some of the pioneering LIBS work was focused on aerosol analysis [1,2], and much of the early experimental and theoretical studies examined the laser-induced breakdown of gases [3]. In recent studies, LIBS has been applied to sample and analyze aerosol populations, including ambient air, using various implementations including single-shot analysis to take advantage of the discrete plasma volume [4][5][6][7][8][9][10]. However, gains in signal-to-noise ratios typically realized with ensemble averaging are not applicable with single-shot analysis, therefore it is important to maximize the signal and precision on a shot-to-shot basis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some of the pioneering LIBS work was focused on aerosol analysis [1,2], and much of the early experimental and theoretical studies examined the laser-induced breakdown of gases [3]. In recent studies, LIBS has been applied to sample and analyze aerosol populations, including ambient air, using various implementations including single-shot analysis to take advantage of the discrete plasma volume [4][5][6][7][8][9][10]. However, gains in signal-to-noise ratios typically realized with ensemble averaging are not applicable with single-shot analysis, therefore it is important to maximize the signal and precision on a shot-to-shot basis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…No significant correlation among crustal elements, anthropogenic metals, and PM 10 in the local pollution event suggests that the crustal elements exist as a small fraction of PM 10 , and various local sources contributed to the increase of such elements, leading to a lack of correlation among them. In a certain local pollution event, it was reported that the PM was correlated well with crustal elements (i.e., Ca) (Hettinger et al 2006). To investigate the difference in distribution of metals among AD and local pollution events in more detail, hourly metal emission lines (Al, Ca, Fe, Mg, Co, Cr, Mn, Pb, and Zn) were analyzed using the chemometric method (i.e., PCA).…”
Section: Resultsmentioning
confidence: 99%
“…Laser induced breakdown spectroscopy (LIBS) can be used for real-time measurements of the elemental composition of aerosols (Cremers et al 1985;Madhavi et al 1999;Neuhauser et al 1999;Cheng 2000;Hahn and Lunden 2000;Fisher et al 2001;Panne et al 2001;Hettinger et al 2006;Mukherjee et al 2006;Kuhlen et al 2008;Park et al 2009;Diwakar et al 2012;Gallou et al 2011). Cremers et al (1985) sampled particles on a filter with subsequent analysis by the LIBS.…”
Section: Introductionmentioning
confidence: 99%
“…It is also hard to classify individual complex biological aerosols at very low concentrations, as well as determine absolute concentrations. Self-absorption of emission, line broadening, and continuum background also affect the usage of LIBS (Beddows and Telle, 2005;Cheng et al, 1999;Hahn et al, 2003;Hettinger et al, 2006;Hybl et al, 2003;Martin et al, 1999).…”
Section: High-discrimination or Identification Techniques For Bio-aermentioning
confidence: 99%